(3GdJMdjd GdYGedj (B:s (3GdfXQjI(B-(3GdJWHjb (B/s - (3HGgj, eUWaj MSjfs; (3YfGf, eMehO YHO GdaJGM s ((3GdbGgQI(B: s (3eQcR GdcJGH ddfTQ(B, s, 2002)
(3eaghe GdJMdjd GdYGedj,HYV GdfXQjGJ GdJj JaSQ GdJMdjd GdYGedj,GdYjfI GdeSJNOeI aj GdJMdjd GdYGedj,Gdbje GdebOQI ddYhGed,GdJMdjd GdYGedj ebGHd GdJMdjd GdYfbhOj hGdJMdjd GdeJYOO,GdbhGfjf GdbGFeI Ydi CSGS GdLPQ GdcGef dGNJjGQ YOO ef GdYhGeds
(3HHdjhZQGajG(B:(3U(B.191(3;cTGa GdeUWdMGJ(B:(3U(B.153-189s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s